The Influence Of Personality And Individual Differences In Improving Employee Performance In Organizations - Sari, Eva Novita; Dwiyanti, Endang; Mandagi, Ayik Mirayanti (Psikologiya Journal, 2024)
Indonesia is one of the developing countries, which means that Indonesia has a lot of human resources. Humans have different personalities or individual characteristics. A normal personality can be described as flexible, while impaired ego function that causes rigidity is considered a sign of personality pathology. In this case, a person's personality varies depending on their habits and environment. According to the theory of Kernberg (1984), lower levels of organizational personality produce emotional instability. Where it can encourage the development of mal-adaptive behavior patterns. Objective: This study aims to identify the personality and differences in each individual that can improve their performance. The method in this study is systematic review. The search for English-language articles sourced from sciencedirect with publication years from 2020 to 2022 which were then reviewed according to the inclusion and exclusion criteria. Based on the results of the systematic review, individual personality cannot be equated with each person because each individual has different habits and environments and can affect employee performance. Low personality accompanied by rumination can exacerbate symptoms of depression. If individuals have high / positive personality traits, it has an important role in improving innovative behavior and performance.